Field-analysis of potable water quality and ozone efficiency in ozone-assisted biological filtration systems for surface water treatment. (1st November 2016) - Zanacic, Enisa; Stavrinides, John; McMartin, Dena W.
Abstract: Potable water treatment in small communities is challenging due to a complexity of factors starting with generally poor raw water sources, a smaller tax and consumption base that limit capital and operating funds, and culminating in what is typically a less sophisticated and robust water treatment plant for production and delivery of safe, high quality potable water. The design and optimization of modular ozone-assisted biological filtration systems can address some of these challenges. In surface water treatment, the removal of organic matter (e.g., dissolved organic carbon – DOC), inorganic nutrients and other exposure-related contaminants (e.g., turbidity and dissolved solids) from the raw water source is essential. Thus, a combination of chemical and biological oxidation processes can produce an effective and efficient water treatment plant design that is also affordable and robust. To that end, the ozone-assisted biological filtration water treatment plants in two communities were evaluated to determine the efficacy of oxidation and contaminant removal processes. The results of testing for in-field system performance indicate that plant performance is particularly negatively impacted by high alkalinity, high organics loading, and turbidity. Both bicarbonate and carbonate alkalinity were observed to impede ozone contact and interaction with DOC, resulting in lower than anticipated DOC oxidation efficiency and bioavailability. The ozone dosage at both water treatment plants must be calculated on a more routine basis to better reflect both the raw water DOC concentration and presence of alkalinities to ensure maximized organics oxidation and minimization of trihalomethanes production. Graphical abstract: Highlights: Small-scale rural water treatment plants present unique challenges. Ozone assistance is vital for biofiltration water treatment with poor quality surface water input. Alkalinity impedes ozone contact and interaction with DOC. When optimized, ozone dosage maximizes oxidation and minimizes trihalomethanes.